PEMBUATAN GAME EDUKASI “MENYUSUN NAMA BUAH DALAM BAHASA INGGRIS TERHADAP ANAK SEKOLAH DASAR” MENGGUNAKAN CONSTRUCT 2 BERBASIS ANDROID - Citra Septiyani; Niki Ratama (Journal of Research and Publication Innovation, 2023)
In learning English, not many teachers use a variety of strategies to create active learning for their students. In general, the learning system that is implemented still adopts the old way, namely the lecture method using the media of books or pictures. Difficulties in learning and understanding vocabulary correct English is a big problem for students. goal. Provide interesting, interactive and easy-to-understand learning and playing tools and not get bored. Make educational games a new innovation and train children's brains by learning to compose words for words.  The research method is Library Studies, Questionnaires, Interviews, Observations with the SDLC Waterfal Method development method. Based on the results of blackbox testing in educational games, arrange fruit names in English, that overall in each view the results of this test are successful or accepted. Because functionally the system can work properly and as expected. All controls in the game can be found easily by the user. This educational game of arranging fruit names in English can help players, especially elementary school students, recognize fruit names in English which gives a feeling of pleasure when learning and playing, assisted by an attractive appearance. as well as good interactivity so that children do not feel bored when learning English vocabulary.